HTML, CSS & JavaScript mobile development for dummies /William Harrel. - Harrel, William
Master the art of designing web pages for mobile devices--a site for small screens! When designing a web page for mobile devices, the big thing is--think small! Your objective is to provide what the mobile user wants without losing the "wow" in your website. This book shows you how to do it using three key technologies. Soon you ll be building mobile pages with forms, quizzes, appropriate graphics, shopping carts